The Legal Configuration of Foreign Tourist Levies as an Instrument for Sustainable Tourism in Bali - I Gede Druvananda Abhiseka; I Gusti Agung Virlan Awanadi; Komang Satria Wibawa Putra; I Putu Edi Rusmana; Muhammad Syahnakri (University of Jember, Indonesia, 2026)
This study aims to analyse the implementation mechanism of the foreign tourist levy policy in Bali Province, compare Bali’s foreign tourist levy policy with similar policies in other countries, and examine strategies to optimise the policy to support sustainable tourism governance. This study employs normative legal research using statutory and comparative approaches. Legal materials were obtained through library research, consisting of legislation, academic journals, books, and relevant policy documents. The findings demonstrate that the implementation of the foreign tourist levy in Bali is supported by a strong legal foundation, including Law Number 15 of 2023 concerning Bali Province, Bali Provincial Regulation Number 6 of 2023, and Bali Governor Regulation Number 36 of 2023. The levy mechanism is implemented through an integrated digital payment system at the main entry points for foreign tourists, with funds allocated specifically to protect Balinese culture and the natural environment. Comparatively, Bali’s foreign tourist levy policy is similar to practices in Bhutan, Japan, Italy (Venice), and the Maldives, particularly in sustainable tourism principles, digitalised payment systems, and conservation-oriented fund management. Nevertheless, Bali possesses distinctive characteristics through the integration of local wisdom values and the active participation of indigenous communities in policy implementation. The optimisation strategy for the foreign tourist levy policy in Bali should therefore focus on regulatory harmonisation, transparent digital governance, institutional strengthening, and indigenous community participation. This study offers novelty by positioning the foreign tourist levy as an integrated legal governance mechanism that combines sustainable tourism principles, local wisdom, and digital governance within the framework of Bali’s regional autonomy. Accordingly, the policy functions not merely as a regional fiscal instrument but also as a legal instrument to promote culture-based and environmentally sustainable tourism governance.